Knockdown of TRIM8 Attenuates IL-1β-induced Inflammatory Response in Osteoarthritis Chondrocytes Through the Inactivation of NF-κB Pathway. (4th August 2020) - Liu, Ruoxi; Wu, Hao; Song, Huanjin
Osteoarthritis (OA) is a degenerative joint disease associated with inflammatory response. Tripartite motif 8 (TRIM8) is a member of TRIM family that has been found to regulate inflammation. The present study was aimed to evaluate the role of TRIM8 in OA chondrocytes. Our results showed that TRIM8 expression was significantly increased in interleukin 1 beta (IL-1β)-stimulated OA chondrocytes. To knock down the TRIM8 expression in chondrocytes, the chondrocytes were transfected with si-TRIM8. Knockdown of TRIM8 attenuated IL-1β-induced production of inflammatory mediators including nitric oxide and prostaglandin E2 . The increased expression levels of inducible nitric oxide synthase and cyclooxygenase-2 in IL-1β-induced chondrocytes were suppressed by TRIM8 knockdown. The IL-1β-induced production of proinflammatory cytokines including TNF-α and IL-6 was significantly decreased after transfection with si-TRIM8. Besides, knockdown of TRIM8 mitigated the IL-1β-induced decrease in aggrecan and collagen-II proteins expression and increase in matrix-degrading enzymes in chondrocytes. Furthermore, TRIM8 knockdown prevented IL-1β-induced nuclear factor kappa B (NF-κB) activation in chondrocytes. Taken together, these findings indicated that knockdown of TRIM8 attenuates IL-1β-induced inflammatory response in OA chondrocytes through the inactivation of NF-κB pathway. Thus, targeting TRIM8 might provide therapeutic treatment for OA.